2019
DOI: 10.1186/s13287-019-1169-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Overexpressing p130/E2F4 in mesenchymal stem cells facilitates the repair of injured alveolar epithelial cells in LPS-induced ARDS mice

Abstract: Background Low differentiation rates of mesenchymal stem cells (MSCs) limit their therapeutic effects on patients in clinical studies. Our previous study demonstrated that overexpressing p130 or E2F4 affected the multipotential differentiation of MSCs, and the underlying mechanism was attributed to the regulation of the G1 phase. Improving the efficiency of MSC differentiation into epithelial cells is considered to be a new method. Therefore, this study was conducted to evaluate the effects of ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…According to Masson's staining or speci c mRNA expression, MSCs overexpressing TGFβ1 did not signi cantly increase pulmonary brosis in ARDS mice. In addition, our previous study also found that mMSCs could further improve the epithelial injury and pulmonary brosis of ARDS mice by increasing differentiation into type II epithelial cells through p130/E2F4 pathway 15 , indicating that there might be no side effects related to MSCs transplantation.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…According to Masson's staining or speci c mRNA expression, MSCs overexpressing TGFβ1 did not signi cantly increase pulmonary brosis in ARDS mice. In addition, our previous study also found that mMSCs could further improve the epithelial injury and pulmonary brosis of ARDS mice by increasing differentiation into type II epithelial cells through p130/E2F4 pathway 15 , indicating that there might be no side effects related to MSCs transplantation.…”
Section: Discussionmentioning
confidence: 88%
“…The mBM-MSC (1×10 6 /well seeded in six-well cell culture plates) were transduced with viral supernatant at a multiplicity of infection (MOI) of 160:1 for 24 hours. Then, the stable cell lines were harvested after selection using blasticidin (BSD; InvivoGen) at the minimal lethal concentration (6 μg/mL) as previously described 15 and cultured in normal culture medium for 20 passages after transduction. Finally, the transduction efficiency of mBM-MSC and the percentage of eGFP-positive cells were evaluated by fluorescence microscopy and flow cytometry (FCM) analysis using a FACSCalibur flow cytometer (Becton-Dickinson, Franklin Lakes, NJ, USA).…”
Section: Lentiviral Vector Transduction and Egfp Reporter Gene Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results pointed to an association of the β‐catenin pathway with E2F‐4. Notably, E2F‐4 was also demonstrated to be involved in inhibiting lung fibrosis …”
Section: Discussionmentioning
confidence: 99%